Learning, Memory, and Transcranial Direct Current Stimulation - Brasil-Neto, Joaquim P. (Frontiers in Psychiatry, 2012)
Transcranial direct current stimulation (tDCS) has been the subject of many studies concerning its possible cognitive effects. One of the proposed mechanisms of action for neuromodulatory techniques, such as transcranial magnetic stimulation (TMS) and tDCS is induction of LTP (long term potentiation) and LTD (long term depression)-like phenomena. LTP and LTD are also among the most important neurobiological processes involved in memory and learning. This fact has led to an immediate interest in the study of possible effects of tDCS on memory consolidation, retrieval or learning of various tasks. This review analyses published articles describing beneficial or disruptive effects of tDCS on memory and learning in normal subjects. The most likely mechanisms underlying these effects are discussed.